Impact of alkaline-earth doping on electronic properties of the photovoltaic perovskite CsSnI3: insights from a DFT perspective. Issue 17 (6th April 2022) - Ornelas-Cruz, Iván; González, Israel; Pilo, Jorge; Trejo, Alejandro; Oviedo-Roa, Raúl; Cruz-Irisson, Miguel
Abstract : Doping the photovoltaic perovskite material CsSnI3  with alkaline-earth species (such as Mg or Ca) could hinder the oxidation of Sn(ii ) to the more stable Sn(iv ), and the resulted compounds could still be suitable for single-junction solar cells. Abstract : The oxidation of Sn(ii ) to the more stable Sn(iv ) degrades the photovoltaic perovskite material CsSnI3 ; however, this problem can be counteracted via alkaline-earth (AE) doping. In this work, the electronic properties of CsSn1− x AE x I3, with x = 0 and 0.25, and AE = Mg and Ca, were investigated via Density Functional Theory. It is proven that the synthetic reactions of all these perovskites are thermodynamically viable. Besides, a slight strengthening in the metal–halide bonds is found in the Mg-doped perovskite; consequently, it exhibits the greatest bulk modulus. Nevertheless, the opposite occurrs with the Ca-doped perovskite, which has the smallest bulk modulus due to the weakening of its metal–halide bonds. The calculated bandgaps for CsSnI3, Mg-doped and Ca-doped perovskites are 1.11, 1.32 and 1.55 eV, respectively, remaining remarkably close to the best photovoltaic-performing value for single-junction solar cells of 1.34 eV. Nevertheless, an indirect bandgap was predicted under Mg-doping. These results support the possibility of implementing AE-doped perovskites as absorber materials in single-junction solar cells, which can deliver higher output voltages than that using CsSnI3 . Finally, it was found that Sr or Ba doping could result in semiconductors with bandgaps close to 2.0 eV.